2006
DOI: 10.1002/jcb.21179
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin‐induced GADD153 upregulation: Modulation by glutathione

Abstract: Abstract:As we reported previously, GADD153 is upregulated in colon cancer cells exposed to curcumin. In the present study, we ascertained the involvement of glutathione and certain sulfhydryl enzymes associated with signal transduction in mediating the effect of curcumin on GADD153. Curcumin-induced GADD153 gene upregulation was attenuated by reduced glutathione (GSH) or N-acetylcysteine (NAC) and potentiated by the glutathione synthesis inhibitor, L-buthionine-(S,R)-sulfoximine (BSO). Additionally, GSH and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Low levels of GSH have been found to decrease resistance of cancer cells to chemotherapeutic drugs [43], boost cell apoptosis [44] and mediate ROS-induced mitochondrial damage [45]. Without knowing the precise site of action, curcumin treatment was associated with decreased intracellular GSH which may account for its pro-apoptotic effects [46] but is inconsistent with the observed anti-oxidant properties of curcumin [47]. Recently, it has been convincingly shown that a number of flavonoids can induce GSH depletion in human tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of GSH have been found to decrease resistance of cancer cells to chemotherapeutic drugs [43], boost cell apoptosis [44] and mediate ROS-induced mitochondrial damage [45]. Without knowing the precise site of action, curcumin treatment was associated with decreased intracellular GSH which may account for its pro-apoptotic effects [46] but is inconsistent with the observed anti-oxidant properties of curcumin [47]. Recently, it has been convincingly shown that a number of flavonoids can induce GSH depletion in human tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, all stimulation of mRNA and protein expressions of CHOP and DR5 was almost completely abrogated by NAC (a ROS scavenger) but only partial reduced by BAPTA (a calcium chelator). In this aspect, previous studies showed that ROS is a molecular mediator inducing CHOP (31,32,46) and DR5 (10, 11, 47) expression.…”
Section: Discussionmentioning
confidence: 92%
“…More recently, other results support the view that curcumin-induced GADD153 gene up-regulation is modulated by ROS generation through the ability of curcumin to neutralize glutathione. Moreover, some involvement of PI3K and PKCd, key parts of an important thiol redox-sensitive cascade, has been also suggested [142].…”
Section: Effects On Signal Transduction Pathwaysmentioning
confidence: 98%